Woman and Home in Iran; The Impact of Ideological Tides through Modernization and Islamization - Nabizadeh, Sima (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Investigating social and political changes in Iran, the outstanding position of women -the one who preserves the indigenous culture and raise the nation- and home -the container of traditions and the nest for the nation to grow within- reveals the women`s position and the domestic realm as two inseparable and pivotal subjects in modernization and Islamization of the Iranian society. The interactive approach between gender identity and spatial identity proposes that any modification of gender identity through any socio-cultural changes, led by either modernization or Islamization forces, will cause changes in spatial identity and vice versa. Through the chronological order of this study, it will be explicated that how different Iranian states have taken different attitudes toward the Woman Question in Iran; hence, the shifting role and identity of Iranian women under the impact of various ideological approaches will be discussed. Moreover, altering the boundary of public and private spheres- as two folded concepts rather than conceptual oppositions- has been evaluated as the convenient and well-related debate to explore the transformation of the Iranian houses through socio-cultural and political changes from late 19th up to the establishment of the Islamic state in Iran. This research reveals that there are similarities in ways through which different state, either modern or Islamic, have tried to promote their agenda by using the woman and the home as the subjects and also the objects of modernization and Islamization.

ÖZ: ‘Modernite’ ve ‘Modernizasyon Süreci’nin İran’da araştırılmasında, geleneği ve özgün kültürü koruyan sıradışı konumuyla ‘kadın’ ve öte yandan tüm bunları barındırma işlevi gören ‘konut/ev’ kadının aile ortamındaki rolüne açıklık getirdikleri için aslında birbirinden kolay ayrılamayan temel konular olarak ortaya çıkarlar. Cinsiyet ve mekan kimliği arasındaki karşılıklı ilişki göstermiştir ki, gerek modernizasyon ve gerekse ‘İslamizasyon’ etkisiyle oluşan sosyo-kültürel değişimlerin cinsiyet kimliğine olan etkileri, mekan kimliğine; ya da mekan kimliğindeki etkilenmeler de cinsiyet kimliğine hep yansımıştır. Dolayısıyla, bu çalışmanın zamansal akışı içinde, farklı devlet yönetimlerinin İran’daki ‘kadın sorunsalı’na yönelik geliştirdikleri farklı bakışlar irdelenmekte, böylelikle İran Kadını’nın çeşitli ideolojik yaklaşımların etkisinde değişen toplumsal rolü ve kimliği tartışılmaktadır. Daha da ötesinde çalışma, karşıt olmaktan çok katlanan kavramlar olarak ele alınan özel ve kamusal alandaki başkalaşımları, İran konutunun 19 yüzyıldan başlayarak günümüze kadar devam eden sosyo-kültürel ve politik değişmelere bağlı dönüşümünü göstermek yolunda elverişli bir tartışma ekseni olarak değerlendirmektedir.
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2017. Supervisor: Assoc. Prof. Dr. Türkan Ulusu Uraz.
Keywords: Architecture; Architecture, Domestic--Houses--Iran; Housing--Architecture and Design--Iran; the woman; the home; modernization; Islamization; Iran